The Jatakatu - Choqueccahua, Jorge (1971)
It is done in Carnivals. Before sunrise, at 3 or 4 in the morning, a member of the family goes to the potato field, carrying a mixture of wine, water, kañiwa, ground corn and sweets called sweet ch'ua. At one in the afternoon, all the members of the family (e.g. of the Choquehuanca family) go out together: parents, uncles, cousins, children..., they go to the farm to the sound of the pinkillo and the drum, hoisting a flag Peruvian.